Waves [videorecording (DVD)] - Shults, Trey Edward; Shults, Trey Edward; Harrison, Kelvin, Jr., 1994-; Hedges, Lucas, 1996-; Russell, Taylor, 1994-; Demie, Alexa, 1994- (Lionsgate, 2020)
Set against the vibrant landscape of South Florida, and featuring an astonishing ensemble of award-winning actors and breakouts alike, this film traces the epic emotional journey of a suburban African-American family, led by a well-intentioned but domineering father, as they navigate love, forgiveness and coming together in the aftermath of a loss. A heartrending story about the universal capacity for compassion and growth even in the darkest of times.